COLLECTIVE REDRESS AND ALTERNATIVE DISPUTE RESOLUTION – REMEDIES IN THE „CONSUMER TOOLKIT” - Monica CALU (Challenges of the Knowledge Society, 2018)
Collective redress for compensation, also known as a group action or a class action, reunites consumers who have suffered the same or very similar loss or harm caused by the same trader. They come in court as a group and seek redress, in one legal claim. Alternative dispute resolution it’s a collective term for the ways that parties can settle a dispute by means of extrajudicial mechanisms with (or without) the help of a third party. Even if these two notions of „collective redress” and „ADR”, at first sight, apparently have little in common, these two topics have become closely related in disputes regarding consumers who have had their rights violated by traders. Even if judicial collective redress procedures cannot be replaced by Alternative Dispute Resolution (ADR) or amicable settlements, we must put aside the assumption that the courts offer the only technique that can deliver redress or that is not possible an amicable settlement procedure for mass claims. Parties in dispute should remain free to recourse to alternative means of dispute resolution before or in parallel to the formal introduction of the judicial claim, taking into account all available options. This study examines the different mechanisms available to consumers to resolve disputes, from private complaints handling to ADR and class actions. This paper aims to analyses the advantages and disadvantages of different approaches to dispute resolution and redress mechanisms, the limits of the out of court settlements and the current situation in the EU Member States, and the cross-border cases and solutions. It also approachesthe enhance and the interconnection of the existing national ADR systems in creation of a powerful unified pan-EU mechanism, provided by Directive 2013/11/EU of the European Parliament and of the council on alternative dispute resolution for consumer disputes.